Evaluation of DNA extraction methods for PCR-based detection of Listeria monocytogenes from vegetables - Vojkovska, H; Kubikova, I; Kralik, P (Letters in applied microbiology, 2015)
UNLABELLED: Epidemiological data indicate that raw vegetables are associated with outbreaks of Listeria monocytogenes. Therefore, there is a demand for the availability of rapid and sensitive methods, such as PCR assays, for the detection and accurate discrimination of L. monocytogenes. However, the efficiency of PCR methods can be negatively affected by inhibitory compounds commonly found in vegetable matrices that may cause false-negative results. Therefore, the sample processing and DNA isolation steps must be carefully evaluated prior to the introduction of such methods into routine practice. In this study, we compared the ability of three column-based and four magnetic bead-based commercial DNA isolation kits to extract DNA of the model micro-organism L. monocytogenes from raw vegetables. The DNA isolation efficiency of all isolation kits was determined using a triplex real-time qPCR assay designed to specifically detect L. monocytogenes. The kit with best performance, the PowerSoil(™) Microbial DNA Isolation Kit, is suitable for the extraction of amplifiable DNA from L. monocytogenes cells in vegetable with efficiencies ranging between 29.6 and 70.3%. Coupled with the triplex real-time qPCR assay, this DNA isolation kit is applicable to the samples with bacterial loads of 10(3) bacterial cells per gram of L. monocytogenes. SIGNIFICANCE AND IMPACT OF THE STUDY: Several recent outbreaks of Listeria monocytogenes have been associated with the consumption of fruits and vegetables. Real-time PCR assays allow fast detection and accurate quantification of microbes. However, the success of real-time PCR is dependent on the success with which template DNA can be extracted. The results of this study suggest that the PowerSoil(™) Microbial DNA Isolation Kit can be used for the extraction of amplifiable DNA from L. monocytogenes cells in vegetable with efficiencies ranging between 29.6 and 70.3%. This method is applicable to samples with bacterial loads of 10(3) bacterial cells per gram of L. monocytogenes.
Keywords: potravinářská mikrobiologie; DNA bakterií; Humans; DNA isolation; Listeriosis; vegetable; Listeria monocytogenes; lidé; Vegetables; zelenina; Food Microbiology; listeriové infekce; DNA, Bacterial; nemoci přenášené potravou; Real-Time Polymerase Chain Reaction; real-time PCR; kvantitativní polymerázová řetězová reakce; inhibition; Foodborne Diseases